Beneficial Therapeutic Approach of Acellular PLGA Implants Coupled With Rehabilitation Exercise for Osteochondral Repair: A Proof of Concept Study in a Minipig Model. Issue 11 (September 2020) - Lin, Chih-Chan; Chu, Chih-Jou; Chou, Pei-Hsi; Liang, Chun-Hao; Liang, Peir-In; Chang, Nai-Jen
Background: Osteochondral (OC) repair presents a significant challenge to clinicians. However, whether the use of acellular spongy poly(lactic-co-glycolic acid) (PLGA) scaffolding plus treadmill exercise as a rehabilitation program regenerates OC defects in a large-animal model has yet to be determined. Hypothesis: PLGA scaffolding plus treadmill exercise may offer improved OC repair for both high and low weightbearing regions in a minipig model. Study Design: Controlled laboratory study. Methods: A total of 9 mature minipigs (18 knees) were randomly divided into the treadmill exercise (TRE) group or sedentary (SED) group. All pigs received critically sized OC defects in a higher weightbearing region of the medial condyle and a lower weightbearing region of the trochlear groove. In each minipig, a PLGA scaffold was placed in the defect of the right knee (PLGA subgroup), and the defect of the left knee was untreated (empty defect [ED] subgroup). The TRE group performed exercises in 3 phases: warm-up, 3 km/h for 5 minutes; main exercise, 4 km/h for 20 minutes; and cool-down, 3 km/h for 5 minutes. The total duration was about 30 minutes whenever possible. The SED group was allowed free cage activity. Results: At 6 months, the TRE-PLGA group showed the highest gross morphology scores and regenerated a smooth articular surface covered with new hyaline-like tissue, while the defects of the other groups remained and contained nontransparent tissue. Histologically, the TRE-PLGA group also revealed sound OC integration, chondrocyte-like cells embedded in lacunae, abundant glycosaminoglycans, a sound collagen structure, and modest inflammatory cells with an inflammatory response (ie, tumor necrosis factor–α, interleukin-6). In addition, in the medial condyle region, the TRE-PLGA group (31.80 ± 3.03) had the highest total histological scores (TRE-ED: 20.20 ± 5.76; SED-PLGA: 10.25 ± 6.24; SED-ED: 11.75 ± 6.50; P = .004). In the trochlear groove region, the TRE-PLGA group (30.20 ± 6.42) displayed significantly higher total histological scores (TRE-ED: 19.60 ± 7.00; SED-PLGA: 10.00 ± 5.42; SED-ED: 11.25 ± 5.25; P = .006). In contrast, the SED-PLGA and SED-ED groups revealed an irregular surface with abrasion, fibrotic tissue with an empty void and inflammatory cells, disorganized collagen fibers, and less glycosaminoglycan deposition. Micro–computed tomography analysis revealed that the TRE-PLGA group had integrated OC interfaces with continued remodeling in the subchondral bone. Furthermore, comparing the 2 defect regions, no statistically significant differences in cartilage regeneration were detected, indicating the suitability of this regenerative approach for both high and low weightbearing regions. Conclusion: Implanting an acellular PLGA scaffold plus treadmill exercise promoted articular cartilage regeneration for both high and low weightbearing regions in minipigs. Clinical Relevance: This study suggests the use of a cell-free porous PLGA scaffold and treadmill exercise rehabilitation as an alternative therapeutic strategy for OC repair in a large-animal knee joint model. This combined effect may pave the way for biomaterials and exercise regimens in the application of OC repair.